Embedded Systems and Software Validation. - Roychoudhury, Abhik (Elsevier, 2009)
Practical debugging and validation techniques for the entire embedded systems design lifecyle!
Keywords: Embedded computer systems -- Design and construction.; Embedded computer systems -- Testing.; Computer software -- Testing.; elektronické knihy; electronic books